Response of tree community composition, plant diversity and aboveground tree biomass in tropical rainforests of Sri Lanka to variation in altitude - H. K. N. Sanjeewani; D. P. Samarasinghe; H. D. Jayasinghe; P. H. Gardiyawasam; W. M. P. S. B. Wahala; W. M. G. A. S. T. B. Wijetunga; K. D. B. Ukuwela; P. Gomes; W. A. J. M. De Costa (Tropical Agricultural Research, 2020)
Tropical rain forests (TRFs) are a major carbon sink and play an important role in regulating the global climate. Floristic composition, structure and carbon storage in biomass of TRFs could vary substantially with climatic and edaphic factors. Altitudinal transects represent an excellent setting for investigating the responses of TRFs to environmental change. Objectives of this study were to determine the variation patterns and possible inter-relationships between plant community composition, diversity and aboveground biomass (AGB) in TRFs across an altitudinal gradient from 134 m to 1,667 m above sea level in Sri Lanka. Five permanent sampling plots of 1 ha each, consisting of four plots in lowland rainforests in Kanneliya and Pitadeniya- Sinharaja Forest Reserves and one plot in the tropical montane forest in Rilagala, were established. Trees with DBH≥10 cm were measured and taxonomically identified. A total of 3,781 trees, belonging to 191 species from 106 genera and 53 families were recorded, with a total basal area of 203.68 m2. Floristic composition of sampling plots showed substantial variation with altitude. Tree density and numbers of species, genera and families and plant diversity indices (i.e. Shannon-Wiener and Simpson’s Indices, evenness and richness of tree species) showed negative curvilinear declines with increasing altitude. Mean DBH, tree basal area and AGB increased from low- (348 kg ha-1) to midaltitudes (762 kg ha-1) and decreased from mid- to highaltitudes (70 kg ha-1), thus showing second-order polynomial relationships with altitude. Similar trends were shown between AGB and tree species number and diversity indices, thus indicating that AGB is maximum at intermediate vegetation diversity.